"Everything Must Match": Detection, Deception, and Migrant Illegality in the India‐Bangladesh Borderlands. Issue 4 (25th September 2019) - Ghosh, Sahana
ABSTRACT: India's militarization of its border with Bangladesh has grown alongside a paranoia around the figure of the "infiltrator" made synonymous with the "Bangladeshi illegal migrant." Set in the borderlands of India and Bangladesh, where ethnic, racial, and linguistic markers do not allow for an easy distinction to be made between the Bengali members of two nation‐states, this article focuses on the paradoxes of documentary citizenship. Residents of these highly surveilled borderlands, as well as a variety of state actors, find that simply possessing identity documents is inadequate amid forgery and deception. The possibility of detection— detectability— of the illegal migrant materializes in India's eastern borderlands across three distinct modes of policing: the interceptive, the judicial‐determinative, and the certificatory. Through an ethnographic exploration of these modes of policing, this article sheds light on the political economy of migrant illegality and reimagines detectability, the infinite and promissory search for the impostor within, as the engine that drives the state. Detectability raises new questions beyond the fetishization of documents and the production and navigation of il/legibility. [ borders, migrant illegality, policing, documents, South Asia ] BENGALI ABSTRACT: 1990s theke Bharat tar Bangladesher songe simantey samarikikaron kromagoto chaliye jachhe. Eki shonge Bharate bere uthchhe "anuprabeshkari" niye ashonka, jar roop Bangladeshi abaidya abhibashi aaj dharon korechhe. Bharat ar Bangladesher simanta elakaye, jekhane bhasha ba jati diye dui desher Bangali sodoshyoder parthokyo chinhito kora shohoj noy, shekhane nana rokom sarkari najardari shadaron manusher dainandin jibonjaopone chhariye porechhe. Simantabasira dekhe je shudhu parichay patra thakle nagarik hishebe shikriti pawa jay na. Shobdhoroner parichay patra jali hoy bole bibhinno sarkari songstha – Border Security Force, Election Commission, police, judge – ebong simantabasira swayang, shobai shondehobhajon chokhe nagorik theke anuprabeshkarike khunje baar korar cheshtai lipto. Ei probondhey ami ei ashesh khonjer alochona kori ebong shei proshonge bartaman Bharate kagojer nagarikottor asongotir byakhya kori. RESUMEN: La militarización de India de su frontera con Bangladés ha crecido junto a la paranoia alrededor de la figura del "infiltrador" hecho sinónimo con la de "migrante ilegal bangladesí". Situados en las zonas fronterizas de India y Bangladés, donde marcadores étnicos, raciales y lingüísticos no permiten una distinción fácil entre los miembros bengalíes de las dos naciones, este artículo se enfoca en las paradojas de la ciudadanía documental. Residentes de estas zonas fronterizas altamente vigiladas, así como una variedad de actores estatales, encuentran que poseyendo simplemente documentos de identidad es inadecuado en medio de la falsificación y el engaño. La posibilidad de detección – detectabilidad – del migrante ilegal se materializa en las zonas fronterizas de la India oriental a través de tres modos diferentes de intervención policial: el interceptivo, el determinativo judicial y el certificatorio. A través de una exploración etnográfica de estos modos de intervención policial, este artículo arroja luz sobre la economía política de la ilegalidad del migrante y reimagina la detectabilidad, la búsqueda infinita y promisoria por el impostor dentro, como el motor que impulsa el estado. La detectabilidad plantea nuevas preguntas más allá de la fetichización de los documentos y la producción y navegación de la i/legibilidad. [ fronteras, ilegalidad del migrante, intervención policial, documentos, Asia del Sur ]